PERBAIKAN SIFAT FISIK DAN KIMIA TANAH LEMPUNG BERPASIR MELALUI APLIKASI BAKTERI Lactobacillus fermentum - Cahya Alam Kusuma; Kurniawan Sigit Wicaksono; Budi Prasetya (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2016)
The ability of sandy loam soils to hold water and nutrients is very low because of unstable soil aggregation. One of soil bacteria that can improve soil aggregates is Lactobacillus fermentum that is able to produce producing exopolysaccharide. The objective of this study was to explore the effect of application of Lactobacillus fermentum on improvement of chemical and physical properties of a sandy loam soil. Lactobacillus fermentum isolated from shrimp paste was used for soil aggregation tests. The treatments were P0 (450 mL distilled water), P1 (100 mL selected media + 350 mL distilled water with 1.67 x 104bacteria), P2 (200 mL selected Â media + 250 mL distilled water with 2.13 x 105 bacteria,Â dan P3 (400 mL selectedÂ media + 50 mL distilled waiter with 3.54 x 106bacteria. The results showed that molasses give the best effect for bacterial growth compared with other media (coconut water, legen and sugar solution). Application of Lactobacillus fermentum significantly increased aggregate stability of the soil studied. In the initial analysis, soil aggregate stability was 0.48 mm (less stable. After incubation period up to 30 days the P1, P2 and P3 treatments increased aggregate stability by 1.27 mm (very stable), 1.43 mm (very stable), and 2.05 mm (very very stable), respectively. Lactobacillus fermentum also gave effect to the increase in organic matter, available P and K available. However, this bacterium did not give effect to an increase in available N and soil pH.